Antimicrobial and Cytotoxic Activity of Cuminum Cyminum as an Intracanal Medicament Compared to Chlorhexidine Gel - Abbaszadegan, Abbas; Gholami, Ahmad; Ghahramani, Yasamin; Ghareghan, Razieh; Ghareghan, Marzieh; Kazemi, Aboozar; Iraji, Aida; Ghasemi, Younes (Iranian Endodontic Journal, 2016)
Introduction: The aims of this study were i) to define the chemical constituents of Cuminum cyminum (cumin) essential oil, ii) to compare the antimicrobial activity of this oil to that of chlorhexidine (CHX) and co-trimoxazole on planktonic and biofilm forms of bacteria isolated from the teeth with persistent endodontic infection and iii) to compare the cytotoxicity of these medicaments on L929 fibroblasts. Methods and Materials: Three groups of microorganisms [aerobic bacterial mixture, anaerobic bacterial mixture and Enterococcus faecalis (E .faecalis)] were isolated from the teeth with persistent apical periodontitis. Zone of inhibition (ZOI), minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), minimum biofilm inhibitory concentration (MBIC) and time-kill tests were performed to assess the antimicrobial efficacy of the medicaments. Further, a cytocompatibility analysis of the medicaments was performed on L929 fibroblasts. The results obtained from disc diffusion test and mean cell viability values of the experimental medicaments were analyzed using two-way and one-way analysis of variance (ANOVA). Results: Seventeen constituents were recognized in cumin oil (predominantly cumin aldehyde and γ-terpinene). Co-trimoxazole showed the greatest ZOI followed by cumin and CHX. The smallest MIC and MBC belonged to co-trimoxazole followed by cumin and CHX for all groups of bacteria except for E. faecalis for which the MBC of cumin was smaller than co-trimoxazole. The results of time-kill assay revealed that all medicaments totally inhibited the bacterial growth in all groups after 24 h. CHX was the most cytotoxic solution while there were no significant differences between the cytocompatibility of different concentrations of cumin essential oil and co-trimoxazole. Conclusion: Cumin exhibited a strong antimicrobial efficiency against the microbial flora of the teeth with failed endodontic treatments and it was biocompatible for L929 mouse fibroblasts. Keywords: Antibacterial Activity; Chlorhexidine; Co-trimoxazole; Cuminum Cyminum; Cytotoxicity; Intracanal Medicament